An Interior Point Parameterized Central Path Following Algorithm for Linearly Constrained Convex Programming - Hou, L.; Qian, X.; Liao, L.Z.; Sun, Jie (SPRINGER/PLENUM PUBLISHERS, 2022)
An interior point algorithm is proposed for linearly constrained convex programming following a parameterized central path, which is a generalization of the central path and requires weaker convergence conditions. The convergence and polynomial-time complexity of the proposed algorithm are proved under the assumption that the Hessian of the objective function is locally Lipschitz continuous. In addition, an initialization strategy is proposed and some numerical results are provided to show the efficiency and attractiveness of the proposed algorithm.